Epilepsy and innate immune system: A possible immunogenic predisposition and related therapeutic implications - Matin, Nassim; Tabatabaie, Omidreza; Falsaperla, Raffaele; Lubrano, Riccardo; Pavone, Piero; Mahmood, Fahad; Gullotta, Melissa; Serra, Agostino; Mauro, Paola Di; Cocuzza, Salvatore; Vitaliti, Giovanna (Human vaccines & immunotherapeutics, 2015)
Recent experimental studies and pathological analyses of patient brain tissue samples with refractory epilepsy suggest that inflammatory processes and neuroinflammation plays a key-role in the etiopathology of epilepsy and convulsive disorders. These inflammatory processes lead to the secretion of pro-inflammatory cytokines responsible for blood-brain-barrier disruption and involvement of resident immune cells in the inflammation pathway, occurring within the Central Nervous System (CNS). These elements are produced through activation of Toll-Like Receptors (TLRs) by exogenous and endogenous ligands thereby increasing expression of cytokines and co-stimulatory molecules through the activation of TLRs 2, 3, 4, and 9 as reported in murine studies.It has been demonstrated that IL-1β intracellular signaling and cascade is able to alter the neuronal excitability without cell loss. The activation of the IL-1β/ IL-1β R axis is strictly linked to the secretion of the intracellular protein MyD88, which interacts with other cell surface receptors, such as TLR4 during pathogenic recognition. Furthermore, TLR-signaling pathways are able to recognize molecules released from damaged tissues, such as damage-associated molecular patterns/proteins (DAMPs). Among these molecules, High-mobility group box-1 (HMGB1) is a component of chromatin that is passively released from necrotic cells and actively released by cells that are subject to profound stress. Moreover, recent studies have described models of epilepsy induced by the administration of bicuculline and kainic acid that highlight the nature of HMGB1-TLR4 interactions, their intracellular signaling pathway as well as their role in ictiogenesis and epileptic recurrence.The aim of our review is to focus on different branches of innate immunity and their role in epilepsy, emphasizing the role of immune related molecules in epileptogenesis and highlighting the research implications for novel therapeutic strategies.